Um Novo Capítulo na Pesquisa em Esports? Mapeamento, Lacunas e os Primeiros Anos dos Esports Móveis na Academia - Tarcízio Macedo (Journal of Digital Media & Interaction, 2022)
This paper develops a systematic review of the international bibliography on mobile esports until September 2021. Its intent is to document the evolution, gaps and the first years of appropriation of this object by the academic community. The approach is guided by complementary mixed methodological procedures, aimed at the organization of knowledge and quali-quantitative in nature. The classification made for this study sought to gather the findings into blocks of analysis, firstly of bibliographic data, and then to build an epistemological/critical appreciation. Among the main results, the small volume of work on the mobile esports segment to date stands out. In the selected material, a low reflection on the subject predominates. Computing is the discipline that stands out, followed by Communication and Sports Sciences.